Genistin and quinolizidine alkaloid induction in L. angustifolius aerial parts in response to mechanical damage - Chludil, Hugo Daniel; Leicach, Silvia R.; Corbino, Graciela Beatriz; Barriga, Lucia G.; Vilariño, M. del Pilar (Taylor & Francis, 2019)
Lupinus species are commonly used as annual forage and for grain production. They are considered alternative crops to soybean due to their adaptation to cool environments and dry soils. The present study is an analysis of the chemical changes coming from biomass removal in a sweet genotype of Lupinus angustifolius. Mechanical damage induced significant increases in antioxidant activity (12.4%), as well as in flavonoid and phenolic content (36.6% and 12.0%, respectively). This sweet lupin also exhibited a higher induced response (68.2%) in the alkaloid content after the damage. These same alkaloids were identified in the control samples and all of them, except lupanine, showed higher relative abundances in response to mechanical damage. Traces of α-isolupanine were detected in control samples and showed a 23.5-fold increase in response to biomass removal. Mechanical damage also produced a striking increase (8.6-fold) in relative abundance of genistin.